Acts of omission and commission in the embodied learning of diasporic capoeira and swimming. (October 2018) - Scott, Susie; Stephens, Neil
This article compares ethnographic experiences of two settings characterised by embodied learning: the African-Brazilian dance/martial-art/game capoeira, and swimming for fitness and leisure, both as practiced in the UK. We consider the ways in which participants in these scenes stage-manage the display of their learning environments, focusing on the rituals and routines of instruction and practice. Applying Scott's (2018) sociology of nothing as an analytical framework, we identify an inverse relationship between two forms of social action. In capoeira, we notice primarily acts of commission (somebodies enacting somethingness), whereas in swimming, we observe more acts of omission (nobodies enacting nothingness), although the distinction is not absolute. In both contexts, we explore the role of space, community, and the body in the negotiation of omissive and commissive socially meaningful action. This relates to Delamont's interests in capoeira, ethnography and learning physical practices outside the classroom.